Patrick Moore's data book of astronomy - Moore, Patrick (Cambridge University Press, 2011)
"Packed with up-to-date astronomical data about the Solar System, our Galaxy and the wider Universe, this is a one-stop reference for astronomers of all levels. It gives the names, positions, sizes and other key facts of all the planets and their satellites; discusses the Sun in depth, from sunspots to solar eclipses; lists the dates for cometary returns, close-approach asteroids, and significant meteor showers; and includes 88 star charts, with the names, positions, magnitudes and spectra of the stars, along with key data on nebulae and clusters. Full of facts and figures, this is the only book you need to look up data about astronomy. It is destined to become the standard reference for everyone interested in astronomy"--Provided by publisher